Model Penguatan Literasi Pariwisata Melalui Perpustakaan Berbasis Inklusi Sosial Selaku Aktor Non-Negara - Zhan, Fuzy Firda (Jurnal Publisitas, 2023)
Literacy is not only about reading and writing activities, but has a broad meaning, including tourism. Furthermore, tourism literacy has currently been developed by the Bahagia Mendawai Pontianak Library as a non-state actor which has various tourism activities paired with literacy activities. The aim of this research is to analyze and put forward ideas in the form of a model for strengthening tourism literacy through libraries based on social inclusion as a non-state actor. This research uses descriptive research methods with a qualitative approach. Data was obtained through interviews and literature studies. The results of this research found that efforts that can be made in this model of strengthening literacy can be done through saprahan culture equipped with facilities such as Literacy Corners. Then activities including discussions related to tourism literacy are then published and promoted via existing social media.